Foliar spraying of boron prolongs preservation period of strawberry fruits by altering boron form and boron distribution in cell - Zhang, Lei; Sun, Changgang; Tian, Hui; Xu, Jiamin; Wu, Xiuwen (Frontiers in Plant Science, 2024)
Boron (B), an essential micronutrient for fruit development, also plays an important role in maintaining the shelf life of strawberries (Fragaria ananassa Duch.) by affecting the cell wall structure and components. We investigated the distribution pattern of B within cells and cell walls in strawberry fruits under different B level and reveal the relationship between the B distribution in cell walls and fruit firmness after harvesting. Foliar spraying of 0.1% H3BO3 promoted the growth of strawberry seedlings, improved fruit yield and flesh firmness by 45.7% and 25.6%. During fruit softening and decay process, the content of bounded B and cell wall-B was decreased while more B was allocated to protoplast and apoplast. The changes of B distribution in cells were attributed to damage of cell during fruit decay, and B extended the freshness period of the fruits by alleviating the decrease of B distribution in cell walls of fruits. After leaving the fruits at room temperature for 10 hours, the B content in different cell wall components also significantly decreased, while foliar spraying of B alleviated the reduction of B content in covalently bound pectin (CBP), cellulose and hemicellulose in fruits. Meanwhile, B spraying to fruit decreased the activity of cell wall degradation enzymes, including polygalacturonase (PG) and pectin lyase (PL), by 20.2% and 38.1%,while enhanced the demethylation of pectin by improving pectin methylesterase (PME) activity from 21.6 to 25.7U/g. Thus, foliar spraying of 0.1% H3BO3 is conducive to enhance the cross-linking of B with cell wall components and maintained cell wall structure, thereby to prolong the shelf life of strawberry fruits.